The potential use of the Internet of Things (IoT) in South African retail businesses - Dlamini, Nomusa Nomhle (Department of Information Systems, 2018)
Technology advancement has resulted in the creation of new paradigms such as the Internet of Things (IoT). The IoT is defined as the interconnectedness of devices or things through a path or network. The IoT is powered by Radio Frequency Identifiers (RFIDs), sensors, actuators, and the internet to enable an anytime, anyplace, with anything and anyone connection. The IoT is perceived as a major technological advancement in history, even though its enabling devices have been in existence for many years. The IoT is moving the digital world into an era where it will power billions of devices bringing about the transformation of products and services offered by businesses. The IoT is predicted to change business processes by the year 2020 while 33% of South African businesses are set to invest in the IoT in the next 3 years. Businesses that will invest in the devices or things that make up IoT are expected to gain more and grow exceptionally well when compared to other businesses in that same market that are not using the IoT. The IoT is changing the retail industry by providing new opportunities to businesses and its customers creating new efficiencies in the business structures resulting in the increase in revenue. The research took a subjective ontological stance with an interpretive view of reality using a deductive approach to theory employing the Technology Organisation Environment (TOE) Framework as a lens for the research. Data for this research was collected using a qualitative research approach using interviews as data collection method. For this research, heads of Information Technology (IT) were interviewed to answer the main research questions which included: 1. What is the potential use of IoT in South African retail businesses? 2. How can the South African retail environment potentially use IoT? 3. What are the potential benefits of using IoT in South African retail businesses? 4. What are the potential challenges of using IoT in South African retail businesses? The findings revealed that retail businesses in South Africa are potentially looking at using the IoT for business processes in the coming years. Currently, retail businesses are not extensively using IoT as the devices and things that power the IoT are not widely available in South Africa. Other barriers that limit uptake is the cost of IoT devices in South Africa and bandwidth. However, respondents stated that the benefits of the IoT outweigh its challenges. The data further revealed that the Return on Investment (ROI) in the IoT will not be realised immediately. Retail businesses are looking at using the IoT for internal business processes rather than customer interaction. Retailers believe that the South African environment is not ready for a fullyfleshed IoT structure such as Amazon Go or Monoprix as the average South African is not technologically savvy. These findings support the TOE Framework that assumes that the technology, organisation, and environment are the driving forces behind a decision to innovate technologically.